Nicomache (Loxochona) lokii sp. nov. (Annelida: Polychaeta: Maldanidae) from the Loki's Castle vent field: an important structure builder in an Arctic vent system - Kongsrud, J.A.; Rapp, H.T. (Polar Biology, 2012)
The discovery of the Loki's Castle vent field at 2,350 m depth on the Arctic mid-ocean ridge in 2008 represents the first known black smoker vent system in the Arctic region. Preliminary results on the benthic invertebrates collected at Loki's Castle indicate the presence of an endemic fauna dominated by tube-building polychaetes, melitid amphipods and gastropods. Here, we formally describe and investigate the ecological role of a new maldanid species, Nicomache (Loxochona) lokii sp. nov., a species found to be particularly common and regarded as a keystone species in this vent system. The description of the new species is supplemented with a DNA barcode. The subgenus N. (Loxochona) includes at present six nominal species, and the new species described herein is the fourth species associated with reducing habitats. A table with diagnostic characters for all species referred to the subgenus is provided. The new species builds tubes up to a length of 20 cm or more, tightly fastened to the substratum. Together with other tube-building species, N. (L.) lokii sp. nov. form a complex three-dimensional habitat for a number of free-living invertebrates. Based on the morphology of the foregut, the microbial community in the gut and the stable isotope values found for this species, it is concluded that it acts as a grazer in this vent system.
World Polychaeta Database (WPolyD. Open access